Convenient Synthesis of Orixiarine: Pharmacological and Biological Perspectives - T. Suresh; K. Velmurugan; P. S. Mohan; R. Nandhakumar (Current Topics on Chemistry and Biochemistry Vol. 4, 2022)
Quinoline alkaloids are a group of an important class of heterocyclic compounds that has grown in significance due to its high level of pharmacological effectiveness and variety of biological functions. An elegant and total synthesis of the quinoline alkaloid, orixiarine was obtained from N-methylaniline and 1-bromo-3- methyl-2-butanone. This research paves the path for the synthesis of newer orixiarine derivatives for future investigation in a number of prospective biological studies.